Petrology and tectonic evolution of late Paleozoic mafic-ultramafic sequences and the Leones Pluton of the Eastern Andean Metamorphic Complex (46-47°S), southern Chile - Rojo, D. (2021)
The metamorphosed mafic-ultramafic sequences of the Eastern Andean Metamorphic Complex outcropping in the Patagonian Andes are critical to disclose the late Paleozoic tectonic evolution of the southwestern margin of Gondwana. In the study area, mafic-ultramafic bodies are thrusted onto polydeformed metasedimentary rocks and intruded by the mid-Carboniferous composite Leones Pluton. The metabasalts (mostly tremolite-chlorite schists and amphibolites) show N-MORB and BABB chemical affinities pointing that formed part of an oceanic crustal section with components of the marginal basin, emplaced after the main pulse of Devonian arc magmatism, possibly in a retreating convergent margin. Interleaved serpentinites consist of serpentine polymorphs (antigorite, lizardite, and late chrysotile) and magnetite, with variably distributed minor amounts of chlorite, tremolite, and traces of ilmenite. Serpentinites have high Cr, Ni, Ti, and Yb contents, and show slightly enriched LREE and flat HREE patterns with a noticeable Eu positive anomaly. Mineralogical and geochemical features indicate that olivine-rich clinopyroxene-spinel-bearing peridotites were metamorphosed in a newly formed east-dipping subduction zone. The closure of the marginal basin continued with the tectonic underthrusting and tectonic juxtaposition of mafic-ultramafic rocks within an accretionary wedge. The tectonic cycle of the oceanic basin finished with the intrusion of mid-Carboniferous subduction-related plutons and pluton-driven thermal metamorphism.